The effect of New Zealand blackcurrant on sport performance and related biomarkers: a systematic review and meta-analysis - Braakhuis, A. J.; Somerville, V. X.; Hurst, R. D. (Journal of the International Society of Sports Nutrition, 2020)
Background: Blackcurrants have come to be regarded as a superfood because of their high polyphenol content, namely anthocyanins. While many berry types have been studied, blackcurrant-anthocyanins may be the superior berry when it comes to athletic performance. The purpose of the review was to evaluate the effects of blackcurrant supplementation on athletic performance, oxidative markers, cognition, and side effects. Methods: Systematic review and meta-analysis. Review manager software (version 5.3) was used for the meta-analysis. The risks of bias was independently assessed using the guidelines and criteria outlined in the Cochrane Handbook for Systematic Reviews of Interventions. The data sources for the search included MEDLINE (Ovid), Google Scholar databases, additional references lists, conference proceedings and grey literature until August 2019. Eligibility Criteria included all blackcurrant (New Zealand derived) interventions, randomised control trials, human participants, placebo-controlled only. Results: A total of 16 separate studies met the criteria for inclusion in the systematic review, with 9 studies contributing to this sport performance meta-analysis. There was an improvement in sport performance when supplementing with blackcurrant, 0.45 (95% CI 0.09-0.81, p = 0.01). The effective dose appears to be between 105 and 210 mg of total blackcurrant anthocyanins, prior to exercise. There were insufficient studies reporting oxidative markers, cognitive effects or biomarkers, and/or side effects to comment on the mechanism of action. Conclusion: Blackcurrant has a small, but significant, effect on sport performance, with no known detrimental side effects.